Pembuatan Alat Permainan Edukatif Wayang Bagi Pembelajaran Di Raudhatul Athfal Se-Kelurahan Kereng Bangkirai Kota Palangka Raya - Sri Hidayati; Muzakki Muzakki; Dwi Puspita; Ismi Hanifah (Universitas Muhammadiyah Semarang, 2024)
The aim of these community service activities is to mentor the teachers and new knowledge about making Eductional Game Tools (APE) for animal and human puppet in RA learning throughout the village of Kereng Bangkirai. The presence of Wayang animals and Wayang Oran's APE is caused by hurdles often encountered at any institution related to media learning in relation to cost issues. With APE, puppet becomes a learning media solution that can be adapted to the topics and learning materials. The method used by this service is Participatory Action Research (PAR). This service was carried out at RA Al-Musafirin in the Kereng Bangkirai district. The result of this activity is the availability of educational gaming tools that are easy to find and use affordable tools and materials for the educational media. In this way, the media is filled to support children's learning in RA.